CO2 Transoral Microsurgery for Supraglottic Squamous Cell Carcinoma - Filippo Carta (Frontiers in Oncology, 2018)
The present study analyzed the results of the endoscopic approach to T1, T2 and selected T3 supraglottic carcinoma with the aim of reviewing functional and oncologic outcomes after different types of endoscopic supraglottic laryngectomies. This is a retrospective clinical study of 42 consecutive patients (mean age of 61.8 years, 33 males, 9 females) treated by the senior author for supraglottic squamous cell carcinoma with a transoral CO2 laser approach and reviewed from November 2010 to September 2017. Surgical procedures were classified according to the European Laryngological Society. In addition to the standardized transoral supraglottic laryngectomies, we introduced a modified type IVb by sparing the inferior third of the arytenoid if not directly involved in the tumor. Swallowing was evaluated with the Swallowing Performance Status Scale reported by the Multinational Association of Supportive Care in Cancer/International Society of Oral Oncology. Survival probabilities were estimated using Kaplan-Meier curves. Two type I, 2 type IIa, 2 type IIb, 3 type IIIa, 12 type IIIb, 13 type IVa, 3 type modified IVb, and 5 type IVb supraglottic laryngectomies were performed. Twenty-one patients (50%) underwent primary neck dissection. The pathologic TNM classification according to the 8th edition of the American Joint Committee on Cancer system was as follows: 9 pT1cN0, 2 pT1N0, 1 pT1N1, 7 pT2cN0, 1 rypT2cN0, 9 pT2N0, 4 pT2N1, 2 ypT2N1, 2 pT3cN0, 2 rypT3cN0, 1 pT3N1, and 2 pT3N2b. Mean follow-up was 3.4 years (range of 9 months to 6 years). According to the Kaplan–Meier analysis, 5-year disease-specific survival, local-relapse-free survival, nodal-relapse-free survival, overall laryngeal preservation and overall survival of patients without previous head and neck radiotherapy/open surgery were 100%, 95.2%, 87.8%, 100%, and 64.6%, respectively. Patients who underwent type I, IIa, and IIb resections (n = 6) started oral feeding the day after surgery, patients who underwent type III-IVb modified resections (n = 31) started oral feeding 3–4 days after surgery, and patients who underwent standard type 4b resections (n = 5) started oral feeding 7 days after surgery. Three months after surgery, patients without a clinical history of previous head and neck radiotherapy/open surgery who underwent type III, IVa, and modified IVb resections showed significantly better swallowing compared to patients who underwent standard type IVb resection: grade 4–6 impairment of swallowing in 8 and 66.7% of cases, respectively (p = 0.006072); patients with a clinical history of previous head and neck radiotherapy/open surgery who underwent type III, IVa, and modified IVb resections showed not statistically significant better swallowing compared to patients who underwent standard type IVb resection: grade 4–6 impairment of swallowing at 3 months in 16.7% and 50% of cases, respectively (p = 0.23568). Transoral CO2 laser supraglottic laryngectomy is an oncologic sound alternative to traditional open neck surgery and chemo-radiotherapy. Recovery of swallowing is significantly worsened after total resection of the arytenoid. Modified type IVb procedure leaving intact, when possible, the inferior third of the arytenoid and consequently the glottic competence, improves functional outcome.